Les bases incarnées de l'institution monétaire. (March 2022) - Bouguereau, Benjamin; Bourgeois-Gironde, Sacha
Money is a fundamental and ubiquitous institution in modern economies. It has the distinctive characteristic of being at the same time a complex social phenomenon and a very easily manipulated object in everyday life. By bringing together works carried out both in cognitive sciences and in philosophy of mind, and while continuing certain classical authors' ideas, this article proposes to conceive money as a cognitive institution whose study would anchor in the paradigm of embodied cognition and extended cognition. Including the study of this artefact into embodied cognition and extended cognition would imply a refusal of any cerebrocentrism, and more broadly, to approach its multiple facets such as its affective dimension in relation to the embodiment of value. Moreover, presenting money as a cognitive institution would mean not only that it would be an extension of certain cognitive processes but also a condition of possibility for others. The cognitive processes in question relate to the objectivation of value in a market society, in order to orient the desire of agents and to the structuring of certain inter-individual actions.